Pengaruh Penerapan Metode Word Square pada Pembelajaran Pendidikan Agama Islam terhadap Hasil Belajar Peserta Didik Kelas V SDK Tompong Kabupaten Manggarai Timur - Astuti Salwiah; M SHABIR U; umar sulaiman (Primer Edukasi Journal, 2023)
The purposes of this study were: 1) To find out how the application of the word square method in learning Islamic religious education to students of grade V SDK Tompong East Manggarai Rgency, 2) To find out how the results of Islamic religious learning for grade V students at SDK Tompong East Manggarai Regencybefore and before the application of the word square method, 3) To find out whether the application of the word square method affects the learning outcomes of Islamic religious education for the fifth grade students of the Tompong SDK, East Manggarai Regency. The type of research used in this research is quantitative with pre-experimental research methods. population in this study was 26 students with the number of samples taken from 26 students. The data collection technique is using a test sheet. The data analysis usd in this study is a sample regression analysis technique with the help of the SPSS 22 application. Based on the descriptive analysis of the average value of the test result for the application of Islamic religious education learning in the material, let’s get to know Allah’s Apostles. The fifthgrade students of the Tompong SDK, East Manggarai Regency before the application of the word square method in the control class after being treated in SPSS were 60.77 and the results of the Islamic religious education learning test for the fifthgrade students of the Tompong SDK, East Manggarai Regency after the application of the word square method in the eksperimental class were 71.54 of the 13 sample or respondents. This shows that based on the average value of the application of the word square method on the learning outcomes of the fifthgrade students of SDK Tompong, East Manggarai Regency, it is included in the high category. There is an effect of the application of the word square method on the learning outcmes for the fift grade students of SDK Topong, East Manggarai Regecy. This canbe seen in the analisysof tests that have been carried out using simple regression using SPSS showing T hit = 2.684 with T tabel = 2.228